2022
DOI: 10.1186/s12966-022-01325-w
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional associations between mental health indicators and social vulnerability, with physical activity, sedentary behaviour and sleep in urban African young women

Abstract: Background Relationships between mental health and multiple health behaviours have not been explored in young South African women experiencing social constraints. The aim of this study was to identify associations between mental health indicators and risk factors with physical activity, sedentary behaviour, and sleep, amongst young women living in Soweto, a predominantly low-income, urban South African setting. Methods For this cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Less than half of the women reported any leisure time physical activity, although 86% of women met physical activity guidelines (based on self-report), but this was typically accumulated through transport-or work-related activity (Prioreschi et al, 2021). Poor quality sleep was reported by a third of the women in this sample, with 19% and 15% were classified as having depression and anxiety respectively, and 24% were at risk for harmful alcohol use (Draper et al, 2022a(Draper et al, , 2022b.…”
Section: Helti South Africa-bukhalimentioning
confidence: 84%
“…Less than half of the women reported any leisure time physical activity, although 86% of women met physical activity guidelines (based on self-report), but this was typically accumulated through transport-or work-related activity (Prioreschi et al, 2021). Poor quality sleep was reported by a third of the women in this sample, with 19% and 15% were classified as having depression and anxiety respectively, and 24% were at risk for harmful alcohol use (Draper et al, 2022a(Draper et al, , 2022b.…”
Section: Helti South Africa-bukhalimentioning
confidence: 84%
“…Given the health disparities between populations across the globe, there have been multiple calls for culturally appropriate interventions, particularly in LMICs, which are grossly underrepresented in the literature [ 10 , 12 , 67 ]. This includes widespread calls to adapt interventions that have demonstrated efficacy and/or effectiveness in a culturally appropriate manner for LMICs [ 13 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pilot data from the Bukhali trial highlight that the social vulnerability of these young women is exacerbated by parity (Ware et al, 2021), food insecurity (Kehoe et al, 2021), and mental health risks (Draper, Cook, et al, 2022). Young black women living in urban low-income settings such as Soweto are particularly vulnerable to being classified as 'NEET' (not in education, employment or training).…”
Section: Healthy Life Trajectories Initiativementioning
confidence: 99%
“…The NEET rate in South African youth (15-24 years) has been increasing over the past 10 years, and has been consistently over 30% (Mudiriza & de Lannoy, 2022). In terms of health behaviours, tobacco use was found in 29% of the pilot sample (Soepnel et al, 2022); less than half reported any leisure time physical activity (Prioreschi et al, 2021), and a third of women reported poor sleep quality (Draper, Cook, et al, 2022). Further qualitative work also drew attention to the relatively low priority given to health, and the "preconception knowledge gap" amongst young women in Soweto (Bosire et al, 2021;Draper et al, 2020).…”
Section: Healthy Life Trajectories Initiativementioning
confidence: 99%